Financial Sector Reforms, Monetary and Output Uncertainties and the Behavior of Money Demand in Kenya: The Divisia Index Approach - Abdullah, Hussin; El-Rasheed, Shehu (Asian Economic and Financial Review, 2019)
The financial sector reforms implemented by the Central Bank of Kenya (CBK) resulted in rapid financial innovation (such as the popular M-Pesa mobile money services) growth, and expansion of several interest earning financial instruments. These developments affect the definition and composition of monetary aggregates, posing a question on the correctness of the current money measures used by CBK. The simple sum aggregates were identified with several theoretical and empirical shortcomings. The rapid financial sector development might affect the stability of money demand function. This study constructs Divisia monetary aggregates for Kenya over the period of 2000’s first quarter to 2015’s third quarter and applies the ARDL method in investigating the stability of money demand function. For the first time, monetary uncertainty and output uncertainty variables are introduced to the Kenyan money demand model. The results reveal that both monetary and output uncertainty has significant influence on money demand in Kenya. This implies that omitting the two variables in the Kenya money demand function might lead to a wrong specification. The money demand function is stable over the period. It means that monetary aggregates targeting is the right framework for monetary policy formulation by the CBK.